Tinjauan Hukum Islam terhadap Kekerasan Seksual Berbasis Elektronik (Telaah Pasal 14 UU No. 12 Tahun 2022) - Annisa Tiara Ramadhani; Hijrayanti Sari; Muttazimah Muttazimah (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2024)
This study aims to determine the criminal law and Islamic law review of electronic-based sexual violence based on article 14 of Law No. 12 of 2022. The type of research used by the author is library research and is categorized as qualitative research. This research uses a normative juridical approach based on the main legal material by examining theories, concepts, legal principles, and laws regulations, where this research emphasizes the use of primary and secondary data. The results showed that the existence of law in the form of Law No. 12 of 2022 concerning criminal acts of sexual violence is expected to provide sanctions and penalties against perpetrators of electronic-based sexual violence in the form of imprisonment and fines. In addition, there needs to be education, awareness, and attention from the government and society to minimize acts of electronic-based sexual violence. When viewed from Islamic law, acts of electronic-based sexual violence are categorized as jarimah takzir because there are no rules and regulations regarding sanctions and laws in the Al-Qur’an and hadith. The punishment for perpetrators of electronic-based sexual violence when viewed from jarimah takzir is fully determined by the judge depending on what category of jarimah takzir can have a deterrent effect on the perpetrator so as not to repeat his actions and for the sake of realizing the benefit of society.